John 15:1-8 - A Re-reading through Earth, SDGs, Covid 19, and Cape Town Farms Contexts - Nina E. Müller van Velden (Perspectiva Teológica)
One of the targets of the United Nations Sustainable Development Goal 6 seeks to ensure equitable sanitation for all by 2030, with a special focus on women and vulnerable groups. However, women working on farms often do not have access to adequate toilets, facing safety, hygiene and privacy issues. These challenges become even more critical in the face of COVID-19 and concerns about new superbugs. In John 15,1-8, Jesus employs vineyard farming imagery to describe the relationship between himself and God the Father, and in turn the relationship between the disciples and himself. In this article, I employ a gender-critical hermeneutical framework, informed by ecofeminist concerns and the intersectionality of gender, race and class, to offer a reading of this biblical passage within the context of Black women working on farms in the Western Cape. I ask to what extent this expectation of submissiveness set by Jesus to his disciples, should be accepted at face value, alongside the use of Earth imagery to implore such submissiveness.